Acceptance of Covid-19 Vaccination in Aceh Province - Rosemary, Rizanna; Ikhsan; Rahmani, Sari (Jurnal Media dan Komunikasi, 2023)
The resistance to Covid-19 vaccination is not solely the community's fault. Educating the public on the importance of vaccination and the prevention of hoax information would contribute to the need for exemplary implementation of vaccination programs in Aceh Province. Insufficient information regarding vaccination to the public has caused many people to refuse vaccination. This study aims to evaluate the health promotion strategy of the Aceh Provincial Health Office in the implementation of Covid-19 vaccination in Aceh through Lawrence Green's (1984) behavioral theory. This qualitative research was conducted by observing and interviewing six Aceh Provincial Health Office informants and analyzing relevant documents. The results of the study indicate that there are factors in the health promotion strategy that shape people's acceptance toward Covid-19 vaccination; (1) including predisposing factors through providing information, forming attitudes and values "‹"‹of beliefs about vaccination in various media platforms; (2) enabling factors through the availability of facilities, medicines, and health workers; and (3) reinforcing factors which manifested in the formation of the supports from community leaders and the availability of policies that support Covid-19 vaccination. The study suggests improving these factors to gain positive responses from the public toward the Covid-19 vaccination program.